The similarities and differences of phraseological sayings and proverbs in the persian and Kazakh languages - Aбдимaевa A. С. (Journal of Oriental Studies, 2017)
This article observes the similarities and distinctions of phraseological sayings and proverbs in the Persian and Kazakh languages. Considering individual features of life and traditions of the Kazakh and Irani people, the analysis of phraseological sayings of two languages is done. The article also contains explanations and examples of phraseological sayings, which are connected to the beliefs and signs of two nations.